Large variability in recommendations for return to daily life activities after knee arthroplasty among Dutch hospitals and clinics: a cross-sectional study - A Carlien Straat; Denise J M Smit; Pieter Coenen; Gino M M J Kerkhoffs; Johannes R Anema; P Paul F M Kuijer (Acta Orthopaedica, 2022)
Background and purpose: Recommendations concerning the return to daily life activities, including work and sport, after knee arthroplasty (KA) are essential for setting realistic patient expectations. Fulfillment of these expectations contributes to more satisfaction and enhanced recovery after KA. However, scientific evidence for such recommendations is limited, and recommendations are often based only on healthcare professionals’ expert opinions. We summarized the current recommendations regarding return to daily life activities provided by Dutch hospitals and clinics to KA patients. Material and methods: Recommendations of 43 Dutch hospitals and clinics were identified, representing the advice provided to 70% of the total Dutch KA patients. Recommendations were retrieved from content from websites (n = 8), brochures (n = 40), and mobile phone applications (n = 9). Results: Recommendations for 24 daily life activities were identified. Individual hospitals and clinics provided recommendations for, on average, 9 (0–15) of these activities. Recommendations varied greatly. For example, recommendations regarding when to resume cycling after KA were provided by 36 of the 43 hospitals and clinics and varied from 3 weeks to 3 months. Interpretation: Recommendations for return to daily life activities are often missing and vary considerably between Dutch hospitals and clinics. These findings show the need for more uniformity across healthcare providers regarding recommendations for postoperative return to daily life activities.